2019
DOI: 10.1002/aur.2132
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy and Autism Severity: A Study of 6,975 Children

Abstract: Epilepsy is known to occur in a higher-than-expected proportion of individuals with autism spectrum disorders (ASDs). Prior studies of this heterogeneous disorder have suggested that intelligence quotient (IQ) may drive this relationship. Because intellectual disability (ID) is, independently of ASD, a risk factor for epilepsy, current literature calls into question the long-understood unique relationship between ASD and epilepsy. Second, data have been unclear about whether developmental regression in ASD is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 53 publications
0
39
1
1
Order By: Relevance
“…Based on Theme 2, epilepsy is the most studied condition, found to be more prevalent in autistic girls/women than in autistic boys/men in most included studies [23,27,28,31,33,35]. However, the complexity underlying this association remains, with studies highlighting potential confounding factors such as heightened autism symptom, language impairment, motor dysfunction, intellectual disability in autistic girls/women [36,37], or multifactorial etiology and shared neurological abnormalities [59]. On the other hand, barriers experienced by girls/women to receive an autism diagnosis [2,4,10] may result in autistic girls/women without evident developmental disabilities being under-represented in the current literature.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on Theme 2, epilepsy is the most studied condition, found to be more prevalent in autistic girls/women than in autistic boys/men in most included studies [23,27,28,31,33,35]. However, the complexity underlying this association remains, with studies highlighting potential confounding factors such as heightened autism symptom, language impairment, motor dysfunction, intellectual disability in autistic girls/women [36,37], or multifactorial etiology and shared neurological abnormalities [59]. On the other hand, barriers experienced by girls/women to receive an autism diagnosis [2,4,10] may result in autistic girls/women without evident developmental disabilities being under-represented in the current literature.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to studies reporting on general health condition prevalence rates including epilepsy mentioned in Theme 1 [27,34], several studies focused specifically on neurological conditions reported a higher prevalence of epilepsy in autistic girls/women compared to autistic boys/men [35][36][37]. Amiet [39].…”
Section: Neurological Conditions Especially Epilepsy Tend To Be Mormentioning
confidence: 99%
See 2 more Smart Citations
“…Epilepsy, which has increased in recognized prevalence in ASD (Spence and Schneider, 2009; Ewen et al, 2019) and many other NDDs, presents several confounds. First, frank seizures can affect both consciousness/the ability to make volitional responses as well as the EEG tracing.…”
Section: Introductionmentioning
confidence: 99%